Wartime Volatility in Coastal Flanders: The Roosewalle Case - Sander Berghmans (Tijdschrift voor Sociale en Economische Geschiedenis)
Warfare in the early modern period almost always coincided with large price shocks. Given that food was a necessity, prices in food markets were particularly prone to such volatility, posing significant challenges for farmers. This issue was especially pronounced for farms in highly commercialized areas like coastal Flanders. In this paper, I will investigate how the Roosewalle farm in coastal Flanders dealt with a volatile price environment in the war-stricken late seventeenth and early eighteenth centuries. Contrary to what one might expect, this paper shows that the Roosewalle farm did not attempt to buffer against volatility by halting production for the market or shifting toward greater self-sufficiency. Moreover, it did not seek to maximize food output during periods of the highest prices, as it was unable to accurately predict price movements. Instead, the farm adopted a strategy of expanding its activities, significantly increasing its sheep flocks and grazing lands to profit from the war in a low-risk manner. To achieve this, the farm also employed multiple strategies to secure sufficient capital. In this way, the Roosewalle farm was able to generate substantial profits during wartime.